PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA BAAMBOOZLE TERHADAP KEMAMPUAN BERPIKIR KRITIS PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Brenda Sylvania, Priscella; Destini, Frida; Nuraini , Siti; Mujiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low critical thinking skills of students in Pancasila Education learning. The study aimed to determine the effect of the Problem Based Learning model assisted by Baamboozle media on the critical thinking skills in Pancasila Education of fourth-grade elementary school students. The study employed a quantitative approach with a quasi-experimental design. The population consisted of all fourth-grade students of SD Negeri 1 Giriklopomulyo, totaling 57 students. The sample was determined using a saturated sampling technique, in which the entire population was used as the research sample consisting of an experimental class and a control class. Data were collected through essay tests and observation. Data were analyzed using simple linear regression and N-Gain tests. The results showed a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. The R Square value of 0.516 indicated that the Problem Based Learning model assisted by Baamboozle media contributed 51.6% to students’ critical thinking skills. Therefore, the Problem Based Learning model assisted by Baamboozle media had a significant effect on students’ critical thinking skills.